Therapeutic Insights into Rubus ulmifolius Schott Leaf Extract: In Vitro Antifungal, Enzyme Inhibition, and Anticancer Activities Integrated with Network Pharmacology and Molecular Docking Analyses of Colorectal and Ovarian Cancer - Amina Bramki (14774747) (2025)
Background/Objectives This study evaluated the antifungal, enzyme inhibitory, and anticancer properties of the ethyl acetate (EtOAc) leaves extract of Rubus ulmifolius Schott using in vitro assays and in silico analysis. Methods Antifungal activity was assessed against five fungal strains by measuring inhibition zones. Enzyme inhibition assays were conducted for acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and urease. Antiproliferative effects were tested against HT-29 colorectal, SK-OV-3 ovarian, and A549 lung cancer cells using the MTT assay. Network pharmacology and molecular docking analyses were performed on major compounds previously identified by GC–MS (gallic acid, caffeic acid, catechin, and fructofuranose) to uncover the potential mechanisms of the plant in colorectal and ovarian cancers. Results The extract displayed notable antifungal activity, particularly against Penicillium sp., Aspergillus fumigatus, and Candida albicans, with inhibition zones of 22.5 ± 0.7 to 26.8 ± 1.3 mm. Enzyme assays revealed moderate inhibition of AChE (IC50 = 92.94 ± 1.97 µg/mL), weaker activity against BChE (IC50 = 274.93 ± 2.32 µg/mL), and modest inhibition of urease (IC50 = 262.60 ± 1.41 µg/mL). The extract exhibited strong antiproliferative effects against HT-29 and SK-OV-3 cells (IC50 = 2.41 ± 0.13 and 4.63 ± 0.26 µg/mL, respectively), whereas activity against A549 lung cancer cells was limited. Network pharmacology predicted 52 and 44 overlapping target genes between the major compounds and colorectal and ovarian cancers, respectively. Protein–protein interaction networks identified hub genes for each cancer type, with key shared targets including EGFR, ESR1, PTGS2, and STAT3. Molecular docking confirmed favorable binding between these targets and the compounds, particularly catechin, which showed interactions comparable to those of reference inhibitors. Conclusions These findings suggest that R. ulmifolius may possess multi-target antifungal, neuroprotective, and anticancer potential, warranting further in vitro pharmacological and preclinical validation. Other Information Published in: Pharmaceuticals License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.3390/ph18101563